Activation of estrogen receptor alpha induces beiging of adipocytes - Roberta S. Santos; Aaron P. Frank; Luciana A. Fátima; Biff F. Palmer; Orhan K. Öz; Deborah J. Clegg (Elsevier, 2018)
Objectives: Brown adipose tissue (BAT) and BAT-like adipose tissues, referred to as 'beige' adipose tissues uncouple respiration from ATP synthesis via uncoupling protein one (UCP-1). There is a sexual dimorphism with respect to beige and BAT tissues; pre-menopausal women have more BAT and are more sensitive to BAT activation than men or postmenopausal women. We hypothesized selective activation of adipose tissue estrogen receptor alpha (ERα) induces beiging of WAT through induction of lipolysis mediated by adipose tissue triglyceride lipase (ATGL). Methods: 3T3-L1 and primary adipocytes were treated with the selective ERα agonist pyrazole triol (PPT), and selection deletion of ERα (using siRNA) was used to determine if selective ERα activation, or inhibition, influences the adipose tissue expression of genes associated with beiging. In a second series of experiments, ERα was selectively added back to adipose tissue of mice lacking total body ERα (ERKO) to determine if add back of ERα changed the morphology of adipose tissue to resemble beige tissues. Additionally, WT and ERKO mice were exposed to cold and FDG labeled glucose uptake was measured to determine the ability of cold to induce UCP-1 in ERKO mice. To begin to mechanistically probe how activation of ERα facilitates beiging, we tested the influence of PPT to activate the lipolytic pathway through ATGL. Finally, since ERα exerts its effects both at the genomic and non-genomic level depending on its cellular location, we determined in vivo if beiging occurs in mice expressing ERα only at the plasma membrane (MOER mice) or only at nucleus (NOER mice). Results: Selective ERα activation by PPT increased markers of beiging in vitro in 3T3-L1 and primary adipocytes, whereas, knockdown of ERα with siRNA reduced the ability of PPT to induce beiging in vitro. ERα add back to the adipose tissue of ERKO mice resulted in multilocular adipose tissue resembling a beige phenotype. Following cold exposure, FDG labeled glucose in BAT tissues of ERKO mice was reduced when compared to weight-matched controls. Glycerol release and ATGL expression were increased after PPT treatment, while pre-treatment with the ATGL inhibitor prevented PPT's ability to increase UCP-1 expression. Finally, MOER mice were more sensitive to beiging of adipose tissues when compared to NOER mice. Conclusion: Our results demonstrate for the first time that selective-activation of ERα in adipocytes increases markers of beiging and this is likely through induction of AMPK and ATGL-mediated lipolysis providing FFAs as a fuel to activate UCP-1. Keywords: Beige adipocytes, Lipolysis, Estrogen receptor alpha (ERα), Obesity, Type II diabetes mellitus (T2DM)